From real to real. Survey and prototyping technologies for the enhancement of cultural heritage - M. Calvano; F. Camagni; T. Talin; E. Ippoliti (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This paper examines a workflow aimed at creating tactile models that enhance the accessibility and understanding of cultural heritage for a broader audience, including individuals with visual impairments. The process involves creating replicas through subtractive prototyping, specifically milling, of a Corinthian marble capital. The replica construction starts with a detailed photogrammetric survey, which is used to guide the milling process for an accurate wooden reproduction. The study emphasises the importance of fidelity between the replica and the original, verifying accuracy by comparing photogrammetric surveys of both. The research highlights the role of tactile models not only as tools for social inclusion but also as a means of preserving cultural heritage by replacing original artefacts exposed to deterioration risks. The methodology demonstrates that combining advanced surveying techniques with CNC prototyping can result in high-quality replicas, suitable for enhancing museum experiences and promoting inclusive cultural participation in line with the Faro Convention and Universal Design principles.